2010
DOI: 10.1126/science.1197257
|View full text |Cite
|
Sign up to set email alerts
|

Large Variations in Southern Hemisphere Biomass Burning During the Last 650 Years

Abstract: We present a 650-year Antarctic ice core record of concentration and isotopic ratios (δ(13)C and δ(18)O) of atmospheric carbon monoxide. Concentrations decreased by ~25% (14 parts per billion by volume) from the mid-1300s to the 1600s then recovered completely by the late 1800s. δ(13)C and δ(18)O decreased by about 2 and 4 per mil (‰), respectively, from the mid-1300s to the 1600s then increased by about 2.5 and 4‰ by the late 1800s. These observations and isotope mass balance model results imply that large va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
143
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 41 publications
(64 reference statements)
19
143
7
Order By: Relevance
“…However, regional scale analyses have consistently failed to show an association between human presence or activities and the amount of biomass burning as shown by charcoal records [Daniau et al, 2010a;Mooney et al, 2011;Marlon et al, 2012;Power et al, in press]. The pre-industrial charcoal record of the past 2000 yrs parallels northern hemisphere temperature changes as reconstructed from multiple high-resolution natural archives [Marlon et al, 2008] and this same pattern has been independently demonstrated for the more recent period , on the basis of stable isotope analyses of carbon monoxide in Antarctic ice [Wang et al, 2010; see also Prentice, 2010]. On a longer timescale, glacial periods have been characterized by less biomass burning globally than during warm intervals [Daniau et al, 2010b;Power et al, 2008].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, regional scale analyses have consistently failed to show an association between human presence or activities and the amount of biomass burning as shown by charcoal records [Daniau et al, 2010a;Mooney et al, 2011;Marlon et al, 2012;Power et al, in press]. The pre-industrial charcoal record of the past 2000 yrs parallels northern hemisphere temperature changes as reconstructed from multiple high-resolution natural archives [Marlon et al, 2008] and this same pattern has been independently demonstrated for the more recent period , on the basis of stable isotope analyses of carbon monoxide in Antarctic ice [Wang et al, 2010; see also Prentice, 2010]. On a longer timescale, glacial periods have been characterized by less biomass burning globally than during warm intervals [Daniau et al, 2010b;Power et al, 2008].…”
Section: Introductionmentioning
confidence: 94%
“…The global incidence of fire decreased during the twentieth century [Marlon et al, 2008;Wang et al, 2010] despite increasing temperatures. This could have been a result of increasing (and increasingly efficient) fire management.…”
Section: Implications Of the Paleo-record Of Firementioning
confidence: 99%
“…carbonyl sulfide, ammonium ion, black carbon, levoglucosan, vanillic acid) in polar ice cores (e.g. Wang et al, 2010Wang et al, , 2012Kawamura et al, 2012;Asaf et al, 2013;Petrenko et al, 2013;Zennaro et al, 2014). Both hemispherically integrated and spatially explicit records of past changes in fire will be used for model evaluation in FireMIP.…”
Section: Carbon Combustibilitymentioning
confidence: 99%
“…As is done here, model studies typically assume that PI biomass burning was greatly reduced (10%) compared to to PD biomass burning and that the geographic distribution is unchanged. However, a recent study of the isotopic composition of CO from an Antarctic ice core suggests that there was more Southern Hemisphere biomass burning in the PI (1700-1850 CE) than the PD (1991 CE) (Wang et al, 2010).…”
Section: Model Limitationsmentioning
confidence: 99%